Gallantry and its discontents: Joan of Arc and virtuous transmasculinity in Radclyffe Hall and Vita Sackville-West. Issue 1 (4th May 2018) - Hovey, Jaime E.
ABSTRACT: The medieval crossdressing warrior Joan of Arc became a popular figure during World War I and its aftermath, appearing in silent films, political posters, plays, novels, and speculative biographies. Her youthful idealism, chivalry, and courage associated her with young soldiers sacrificed on the field of battle, and her canonization in 1920 made official the centuries-old veneration of her as a virgin martyr. Modern figurations of Joan emphasize the ethical dimensions of her transmasculinity, where queer gender identity and desire are actively engaged in the struggle to build a more tolerant world. Looking at Cecil B. DeMille's film Joan the Woman (1916), Radclyffe Hall's novels The Unlit Lamp (1924) and The Well of Loneliness (1928), and Vita Sackville-West's biography Saint Joan of Arc (1936), I argue that Joan's chivalry and saintliness model an ethical transmasculine gender that emerges in wartime, but gradually shows up elsewhere in modernism to insist on queer social justice, fighting "for the good of all."